A narrative literature review: the application of video games as therapeutic tools for psychological therapy. (December 2021) - Mahon-Daly, Sean; Jeyasingam, Neil
Objectives: Video games (games played by electronically manipulating images produced by a computer programme on a screen) are being developed with a specific focus on treating mental health. This narrative review briefly discusses the history of video games and mental health. It then provides a critical discussion on the application of video games as therapeutic tools, then discusses the notion of 'serious games' ( games designed for a primary purpose other than entertainment) and their applicability. Conclusions: Serious games have preliminary evidence to support their use practically in the clinical treatment of mental illness. Future randomised control trials are necessary to further explore their efficacy and potential areas of application.